Otimização para o acionamento de sistemas yaw em turbinas eólicas - Ferreira, Gonçalo Machado (Universidade Federal Rural do Semi-Árido, 2018)
Reliability studies have shown that the yaw system is the second mechanical component in failure rate and most contributes to a general downtime of wind turbines. The impact of this reality is set in significant cost increases, which are confirmed by surveys that present a cost trend analysis in wind turbines, showing that the yaw system cost trend exponent is the second largest. In state-of-the-art wind turbines, the yaw system is now run with four gearboxes in standard operation - or in multiple numbers. This ensures uniform distribution of the load for each yaw reducer, avoiding undesired overloads on the individual units. However, today there are modern wind turbines, with expected long-term operations, which are not grouped into these new configurations. Typically, these yaw system structural models consist of a configuration of three motor reducers, a design typically characterized as inefficient to cope with high starting inertial loads. Due to structural characteristics, the addition of a fourth geared motor to these turbines is not possible. With this scenario, alternative solutions solve the impasse. Thus, the present work proposed an optimization for the activation of yaw systems: through the use of microprocessed static starters (soft-starter), achieving a marked reduction of the efforts on transmission devices (gearboxes, pins, gears) of the yaw system. At first the yaw system of study was defined, from its configuration to technical data essential for the project. With the analysis of these load data applied in simulation software, it was possible to define the appropriate soft-starter for use. The next step was to study the control and power system of the turbine, in order to elaborate a feasible electrical project the proposed changes, preserving the operational processes of the wind turbine.
Monografia
Keywords: Turbinas eólicas; Sistema yaw; Energia renovável; ENGENHARIAS::ENGENHARIA ELETRICA